2010
DOI: 10.1089/acu.2009.0715
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture and Electroauriculotherapy Treatment for Infertility

Abstract: Background: Acupuncture and electroauriculotherapy treatments may enhance the success rate of the embryo implantation stage of in vitro fertilization (IVF) in the treatment of infertility due to hormonal imbalances. Objective: To examine the integrated approach of acupuncture and electroauriculotherapy as an adjunct to fertility medication and IVF. Design, Setting, and Patient: A case report of a 33-year-old woman who was in the beginning of her third IVF cycle, who presented to a private clinic and received a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In recent years, acupuncture is more and more popular in the management of subfertility, but its effectiveness has remained controversial [1]. Some studies showed that acupuncture was significant in improving IVF outcomes [2,3,4]. The specific rationales were displayed as follows.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, acupuncture is more and more popular in the management of subfertility, but its effectiveness has remained controversial [1]. Some studies showed that acupuncture was significant in improving IVF outcomes [2,3,4]. The specific rationales were displayed as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Second, acupuncture may enhance blood flow of the uterus and reduce uterine artery blood flow impedance [7]. Third, acupuncture treatment may enhance the hormonal balance of the embryo implantation stage of IVF in the treatment of infertility [4]. Another study also showed that acupuncture may promote the release of neurotransmitters, thereby mediating the development of hormones [8].…”
Section: Introductionmentioning
confidence: 99%